A case report of heart failure after therapy with ustekinumab - Kourosh Beroukhim; Melissa Danesh; Catherine Nguyen; John Koo; Argentina Leon (Wolters Kluwer Medknow Publications, 2015)
Psoriasis is a chronic immune disorder that affects 2-3% of the US population. Ustekinumab, a monoclonal antibody against IL-23/12, has shown great efficacy in treating psoriasis. Here we present a rare finding of a patient with plaque-type psoriasis who was diagnosed with congestive heart failure after initiating treatment with ustekinumab. The patient experienced full recovery of cardiac function upon discontinuation of ustekinumab.